DIFFERENTIAL DIAGNOSIS OF MYOCARDIAL ISCHEMIC INJURY IN CONDITIONS OF PERMANENT CARDIAC PACING - B. G. Iskenderov; T. V. Lokhina; A. A. Minkin (Российский кардиологический журнал)
A dynamics and origin of changes in the end part of spontaneous ventricular complexes has been studied in 109 patients with permanent ventricular pacing. Pacemaker inhibition test and potassium test have been shown to increase the detection rate of true functional Chaterier syndrome characterized by ST depression and T wave inversion in spontaneous QRS complexes in leads II, III, aVF and V2-V6 , from 39. 9 % to 72. 6 % cases. This allows to rule out non-Q wave myocardial infarction overdiagnostics in this subset of patients. Furthermore, other non-coronary causes for ECG changes need to be sought (pericarditis, cardiomyopathies, myocardiodystrophies etc. ) in permanent pacing.